EMPIRICAL STUDY ABOUT THE RELATION BETWEEN FAMILY OWNERSHIP AND FIRM PERFORMANCE: EVIDENCE FOR ROMANIAN FAMILY FIRMS - BEBEȘELEA, Mihaela; TRANDAFIR, Adina (Annals of Spiru Haret University. Economic Series, 2022)
The objective of the article is to produce and validate a statistical model for quantifying the performance of family firms. Such aim will be achieved through the analysis of a sample of 27 entities from the “family firms from Romania” group. The statistical hypothesis underlying the specification of the model is one according to which selected variables will distinguish the performing family firms from the non-performing ones, regardless of ownership. The article addresses an alternative possibility for assessing the financial performance of family businesses, namely a model created by Carton, R. The complex indicator created by Carton, R, is composed of performance factors such as asset growth, debt change and degree change survival rate (Z-score change), calculated using the Statev coefficient, Z-score. The indicators that were used are extracted from both the Entities’ Balance Sheet and their Profit and Loss Account (on-line), while the modelling is carried out through the Excel statistical modelling.